Homogenization of sandwich structures - Rabczuk, T.; Kim, J. Y.; Samaniego, E.; Belytschko, T. (International journal for numerical methods in engineering, 2004)
A homogenization method is proposed for sandwich structures consisting of two plates interlaced with beams and shells in a periodic, lattice structure. The proposed method is a quasi‐continuum approach where the constitutive response is obtained from the generalized forces of the interlacing elements. Buckling is studied as part of this model. Comparison of the homogenized model with fully discrete models show reasonable to very good agreement. Copyright © 2004 John Wiley & Sons, Ltd.